Pengaruh Disiplin dan Motivasi Kerja terhadap Kinerja Karyawan Tunaiku PT. Amar Bank Indonesia divisi CRO - Intan Ananda Rianty; Siti Nurjanah (KALBISIANA Jurnal Sains, Bisnis dan Teknologi, 2022)
This study describes the influence of work discipline and work motivation in a company with the impact on employee performance variables. The object of this research is PT. Amar Bank Indonesia. The purpose of this study is (1) to determine and analyze the effect of work motivation and work discipline on employee performance. (2) to determine and analyze the variables that have a dominant influence on employee performance. The data obtained in this study is primary data by distributing questionnaires to respondents. This study uses a quantitative method through a survey questionnaire distributed via google form to 40 respondents which is then processed using SPSS version 20.0 with the sampling method is saturated sampling technique. The results of hypothesis testing (t test) that work discipline has a significant effect on employee performance with a t count of (4.255) T table (1.971). work motivation has a significant effect on employee performance with t count of (5.374) T table (1.971) with a coefficient of determination of 94%. Work motivation and work discipline have a significant effect simultaneously on employee performance. The implications of this research can provide understanding for researchers to pay attention and build work motivation and good work discipline for PT. Tunaiku Amar Bank Indonesia.